Formulation and Evaluation of Niosomes of Benzyl Penicillin - Onochie I.T.O., Nwakile C.D., Umeyor C.E., Uronnachi E. M., Osonwa U. E., Attama A.A., and Esimone C.O. (Journal of Applied Pharmaceutical Science, 2013)
Benzylpencillin niosomes were formulated using thin film hydration technique. The resultant niosomes were evaluated using surface morphology, particle size and its distribution, encapsulation efficiency, In vitro drug release, in vivo bioavailability and In vitro antimicrobial activity parameters. Both short (3 h) and long term (24 h) stability studies were carried out on the formulations. The lipid-surfactant ratio and the presence of co-surfactant were identified as the key variables that affect performance of the formulations. The niosomes particle sizes were between 1.67μm to 2.22 μm. The encapsulation efficiency was found to be highest in batch A with value of 82.42 %. Batches B and C exhibited slow release, oral stability and good bioavailability in vivo. For In vitro and in vivo studies, batch B containing span 80,Tween 65 and cholesterol was particularly stable and released its drug content in a controlled manner. The Cmax for the batches were higher than that of pure drug which has value of 55.04 mg/ml in vivo. The IZD of the batches were high against the test micro organisms and all the batches exhibited antimicrobial activities greater than the unformulated drug against S. typhi, P. vulgaris and Ps. Aereuginosa.
Keywords: Niosomes, Benzyl penicillin, Cholesterol, Surfactant, Co-surfactant.